Early Left Ventricular Systolic and Diastolic Dysfunction in Patients with Newly Diagnosed Obstructive Sleep Apnoea and Normal Left Ventricular Ejection Fraction - Lisulov Popovic Danica; Mirjana Krotin; Marija Zdravkovic; Ivan Soldatovic; Darko Zdravkovic; Milica Brajkovic; Vera Gardijan; Jelena Saric; Ruzica Pokrajac; Dragan Lovic; Predrag Stevanovic; Milina Tancic Gajic; et al. (The Scientific World Journal)
The aim of the study was to evaluate whether obstructive sleep apnea (OSA) contributes directly to left ventricular (LV) diastolic and regional systolic dysfunction in newly diagnosed OSA with normal left ventricle ejection fraction. Methods. 125 consecutive patients were prospectively enrolled in the study. Control group consisted of 78 asymptomatic age-matched healthy subjects who did not have any cardiovascular and respiratory diseases. All patients had undergone overnight polysomnography and standard transthoracic and tissue Doppler imaging echocardiogram. Results. The E/A ratio and the peak E wave at mitral flow were significantly lower and the peak A wave at mitral flow was significantly higher in OSA patients compared with control subjects. Left ventricle isovolumetric relaxation time (IVRT) and mitral valve flow propagation (MVFP) were significantly longer in OSA patients than in controls. Tissue Doppler derived S′ amplitude of lateral part at mitral valve (S′Lm) and E′ wave amplitudes both at the lateral (E′Lm) and septal parts of the mitral valve (E′Sm) were significantly lower in OSA patients compared to controls. Conclusion. Newly diagnosed OSA patients with normal global LV function have significantly impaired diastolic function and regional longitudinal systolic function. OSA is independently associated with these changes in LV function.